Flock size and egg production performance of backyard chicken reared by rural woman in Peshawar, Pakistan - Javed, K.; Farooq, M.; Mian, M.A.; Durrani, F.R.; Mussawar, S. (2003)
A study was conducted during the year 2000 to investigate flock size and egg production performance of backyard chicken maintained by woman in rural areas of Peshawar, NWFP, Pakistan. One hundred and thirty female farmers were selected at random from 13 randomly selected nearby villages of Peshawar city.